Back Cover: Vesicle Structures from Bolaamphiphilic Biosurfactants: Experimental and Molecular Dynamics Simulation Studies on the Effect of Unsaturation on Sophorolipid Self‐Assemblies (Chem. Eur. J. 21/2014). Issue 21 (14th May 2014) - Dhasaiyan, Prabhu; Pandey, Prithvi Raj; Visaveliya, Nikunjkumar; Roy, Sudip; Prasad, B. L. V.
Abstract : Understanding the self‐assembly of vesicles is important because they are involved in the construction of cell walls in some naturally occurring micro‐organisms. In the Communication by S. Roy and B. L. V. Prasad et al. on page 6246 ff., experimental and molecular dynamics studies show that sophorolipids based on linolenic acid (which fit into the classification of asymmetric bolaamphiphilic lipids) self‐assemble into giant‐vesicle‐type structures. The cell walls of these vesicles consist of a double bilayer wherein the molecules are arranged in a tail–head–head–tail manner in each bilayer.